The impact of technology on vocabulary acquisition among adult efl learners. - Fernandez Sinchiguano, Miguel Fernando (2025)
This research project analyzes the impact of technological tools on vocabulary acquisition among adult learners of English as a foreign language (EFL) in the Ecuadorian context. The overall objective was to observe the use of these tools in the classroom and propose a more effective approach to improving vocabulary acquisition. The methodology combined quantitative and qualitative approaches, using online questionnaires and semi-structured interviews with teachers and students. The results showed that technological tools and platforms are effective in increasing motivation and vocabulary retention, especially when integrating gamification elements and immediate feedback.